The Cabin Crew Blues. Middle-aged Cabin Attendants and Their Working Conditions - Bergman, Ann; Gillberg, Gunnar (Nordic Journal of Working Life Studies, 2015)
This article examines how an airline company uses the labor of a group of middle-aged cabin attendants in an industry increasingly characterized by deregulation and competiveness. The study was based on in-depth interviews with seven women, all with between 24 and 30 years of work experience as cabin attendants. The article focuses on the women’s working conditions and well-being and the analysis reveals three key aspects—intensification of work, vulnerability, and aging—that affect the cabin attendants’ experiences and emotions in relation to the work. It is at the intersection of these three aspects that the cabin attendants’ concerns must be understood. The study’s findings indicated that positive emotions such as job satisfaction and commitment have diminished because of exploitative and otherwise poor working conditions. Taking the cabin attendants’ concerns as its point of departure, the article shows that there is a need to move away from a discussion about emotional labor toward a discussion of working conditions.